Pimentão (Capsicum annuum) fertilizado com composto orgânico e irrigado com diferentes lâminas de irrigação - Cardozo, Mirian Tavares Dias [UNESP]; Galbiatti, João Antonio; De Santana, Márcio José; Caetano, Mayra Cristina Teixeira; Carraschi, Silvia Patrícia; De Nobile, Fabio Olivieri (Brazilian Journal of Irrigation and Drainage - IRRIGA, 2016)
Irrigation and fertilization are determining factors in vegetables’ productivity, mainly when correct doses are applied to obtain high productivity. Fertilization with organic composts is a feasible option, because it contributes to reduce production costs, improves productivity and is good to the environment. The objective of this study was to evaluate the effects of fertilization with organic waste compost in the productivity of green sweet peppers irrigated in a protected environment. The experimental design was randomized blocks with 24 treatments, factorial 6 × 4, being six fertilizations (mineral, organic with the dosages 4, 8, 12 e 16 t ha-1 and control) and replacement of water (70, 100, 130 e 160%) to take the soil to field capacity, with tree repetitions and six plants each replicate. Among the results it was verified that when water replacement was made in full (100%) the average number of fruits was similar for mineral fertilizer and fertilization with organic compost of 8 t ha-1, 12 t ha-1 and 16 t ha-1, showing the feasibility of the use of these compounds in this culture.
Green pepper (Capsicum annuum) fertilized with organic compound and different water depths
Keywords: Evapotranspiration; Management; Protected environment; Vegetables; Water replacement